2017
DOI: 10.1051/cagri/2017028
|View full text |Cite
|
Sign up to set email alerts
|

Climate-smart cropping systems for temperate and tropical agriculture: mitigation, adaptation and trade-offs

Abstract: -Climate-smart cropping systems should be designed with three objectives: reducing greenhouse gas (GHG) emissions, adapting to changing and fluctuating climate and environment, and securing food production sustainably. Agriculture can improve the net GHG emissions balance via three levers: less N 2 O, CH 4 and CO 2 emissions, more carbon storage, and green energy production (agrifuels, biogas). Reducing the application of mineral N fertilizer is the main option for reducing N 2 O emissions either directly or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 87 publications
0
25
1
1
Order By: Relevance
“…Farmers willing to pay for all climate information and services tended to be younger people or non-educated. This contradicts the results of other authors [7][8][9][10][11][12][13][14][15][16][17][18][19] who reported that age has a positive effect on the WTP for climate information demand in Ghana and Burkina Faso. Zongo et al [7] showed that education of farmers positively influences the demand for CIS.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Farmers willing to pay for all climate information and services tended to be younger people or non-educated. This contradicts the results of other authors [7][8][9][10][11][12][13][14][15][16][17][18][19] who reported that age has a positive effect on the WTP for climate information demand in Ghana and Burkina Faso. Zongo et al [7] showed that education of farmers positively influences the demand for CIS.…”
Section: Discussioncontrasting
confidence: 67%
“…It is often based on generations of experience and includes both biophysical and mystical indicators [6]. With the increase in rainfall variability and climate extreme events (such as droughts, floods and strong winds) as consequences of climate change in the Sahel [8], the endogenous forecasts, are becoming less reliable [7]. This means that climate change is bringing and increasing risk and uncertainty on agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…Some American and European countries have already diversified livelihoods, harvested rainwater or used alternative livelihoods for fishing by developing change-resistant hybrids, as a mean to face climate change, especially among farmers in diverse tropical and subtropical areas all over the world (Curcic et al, 2018). This should generate new opportunities but also lead to limitations arising from various factors of not only environmental and technological character, but also of political and market factors (Schroth and Ruf, 2014;Debaeke et al, 2017). Diversification strategies can be defined on different bases including:…”
Section: Planting and Harvesting Changesmentioning
confidence: 99%
“…Climate change causes a major stress on livestock production [9] and it affects the quantity and quality of forage crops. The mitigation of stress in forage cropping systems varies for specific regions [10,11], such as Europe and China [12], and optimum management practices include cow and calf and dairy cows under the variable climatic conditions during summer and autumn in the region, and triple forage cropping system over a couple of years should be determined to evaluate the feasibility of the cropping system in southern Kyushu, Japan.…”
Section: Introductionmentioning
confidence: 99%